Abaca fibre reinforced PP composites and comparison with jute and flax fibre PP composites (eXPRESS Polymer Letters)
Abaca fibre reinforced PP composites were fabricated with different fibre loadings (20, 30, 40, 50wt% and in some cases 35 and 45 wt%). Flax and jute fibre reinforced PP composites were also fabricated with 30 wt% fibre loading. The mechanical properties, odour emission and structure properties were investigated for those composites. Tensile, flexural and Charpy impact strengths were found to increase for fibre loadings up to 40 wt% and then decreased. Falling weight impact tests were also carried out and the same tendency was observed. Owing to the addition of coupling agent (maleated polypropylene -MAH-PP), the tensile, flexural and falling weight impact properties were found to increase in between 30 to 80% for different fibre loadings. When comparing jute and flax fibre composites with abaca fibre composites, jute fibre composites provided best tensile properties but abaca fibre polypropylene composites were shown to provide best notch Charpy and falling weight impact properties. Odours released by flax fibre composites were smaller than jute and abaca fibre composites.